SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL STUDIES OF M(II) COMPLEXES WITH2,3- BUTANEDIONE-3-MONOXIME - H. RAJURKAR, VAISHALI (Innovare Journal of Sciences, 2020)
Objective: Various Schiff bases and their metal complexes have wide applications in various fields such as pharmaceuticals, analytical, clinical, biological etc due to theirbiological activity such as antibacterial, antifungal, anticancer, antidiuretic, antioxidant etc. Materials and Methods: Reaction between 2,3-Butanedione-3-monoxime, 3/4-hydroxyphenyl and some hydrated metal salts of MnII gives complexes of the type [MnL22(H2O)].The ligands and the complexes were characterized by elemental analysis, magnetic susceptibility measurements and spectral (I.R., U.V.-Vis., N.M.R.) analysis.Anti-bacterial and anti-fungal activity of the schiff base ligands and their metal complexes have been studied using the agar well diffusion method and ditch diffusion method. Results:Spectroscopic study showsbidentate ligands and coordination occurs through oxime oxygen after deprotonation and nitrogen of azomethine group.Ligands and metal complexes shows activity against S. aureus (gm positive), P. aeruginosa (gm negative), Aspergillusniger and Candidaalbicans. Conclusion: The spectral and magnetic study suggests octahedral geometry for metal complexes.Metal complexesacts asmost promising antifungal and antibacterial against Staphylococcus aureus and Pseudomonas aeruginosa as compared to Schiff bases.